Technical and environmental study of calcium carbonate looping versus oxy-fuel options for low CO2 emission cement plants. (August 2018) - Rolfe, A.; Huang, Y.; Haaf, M.; Pita, A.; Rezvani, S.; Dave, A.; Hewitt, N.J.
Graphical abstract: Highlights: The CCL CO2 capture process and oxy-fuel cement plant were modelled and analysed. LCA had been conducted to determine the environmental impact. CCL and oxy-fuel CO2 capture rates of 94% and 100% were found, respectively. The specific CO2 avoided in the CCL is higher than in the oxy-fuel cement plant. The grid electricity CO2 emission factor affects the CCL and oxy-fuel performance. Abstract: The process of cement production emits large amounts of CO2 through both chemical reactions and fossil fuel combustion. Reducing CO2 emissions from the cement industry is becoming a global imperative. This work focuses on the technical and environmental evaluation for the integration of calcium carbonate looping (CCL) and oxy-fuel combustion processes into a cement plant for carbon capture and storage. Three scenarios have been established: 1. the base case cement plant without CO2 capture, 2. Cement plant with integrated CCL and 3. Oxy-fuel cement plant. The process models of the CCL capture plant and the oxy-fuel cement plant are developed. To better understand the technical parameters and benefits of each scenario, the ECLIPSE modelling software is used to a technical analysis. Life cycle analysis (LCA) has been conducted using the SimaPro software to determine the environmental impact of the capture technologies. Technical results showed that the cement plant equipped with the CCL illustrated better performance with specific CO2 emissions avoided of 1.21 t CO2 /tClinker and the specific primary energy consumption of 2.39 GJ/t CO2 compared with the oxy-fuel cement plant with 0.71 t CO2 /tClinker and 3.31 GJ/t CO2 . The main conclusion indicated that the CCL unit had a lesser environmental impact than the oxy-fuel combustion because of the additional benefit of electricity generation through the heat recovery system.